Coping With Stress and Psychological Resilience Among Relatives of Patients in Coronary Intensive Care Unit: A Descriptive and Correlational Study - Sema Yılmaz; Nevin Onan (Yoğun Bakım Hemşireliği Dergisi)
Objective: This study aimed to determine the stress coping styles and psychological resilience of relatives of patients in the coronary intensive care unit. Materials and Methods: This descriptive study was carried out with 205 relatives of patients in the coronary intensive care unit. Information Form, Coping Ways Scale (WCS), and Psychological Resilience Scale for Adults (PRS-A) were data tools. The data were evaluated with descriptive and correlational analysis. Results: The WCS subscale mean scores of the patient relatives; it was found that the mean score for the self-confident approach (SCA) was 2.23±0.39, the optimistic approach (OA) was 2.16±0.41, social support-seeking (SSS) was 2.14±0.44, the helpless approach (HA) was 1.38±0.38, and the submissive approach (SA) was 1.31±0.35. It was found that the total score of the PRS-A was 3.83±0.54. The highest scoring subscale of PRS-A was the Family Integrity (4.20±0.74). The sub-dimension with the lowest score was the Future Perception (2.31±0.44). It was found that there was a relationship between PRS-A total and subscale scores and SCA, OA, and SSS subscales, and that this relationship was moderately positive (for each p < .01). A relationship was determined between PRS-A total and subscale scores and HA and SA subscales. This relationship was moderate and negative (for each p < .01). Conclusion: In conclusion, psychological resilience increases effective coping in the relatives of patients in the coronary intensive care unit. Interventions that increase psychological resilience are needed to help relatives of the patients cope more effectively with stress.